Formulation and Evaluation of Mucoadhesive Buccal Patches Containing Cisplatin for Oral Cancer Therapy - Sahu, Renuka; Sahu, Gyanesh Kumar; Sharma, Harish; Patel, Devid; Nirala, Rakesh Chand; Dewangan, Bhaskar; Sahu, Gaurav Kumar; Choubey, Suyash; Wamankar, Suchita; Sahu, Anjali (International Journal of Aquatic Research and Environmental Studies, 2026)
Oral cancer is a highly prevalent disease affecting millions worldwide. Major risk factors for oral cancer include tobacco and alcohol use, HPV infections, poor nutrition, and genetic susceptibility. The disease progresses through multiple genetic and epigenetic alterations involving tumor suppressors like p53, p16, and FHIT, along with oncogenes like EGFR, c-yc, K-ras, int-2, PRAD-1, and bcl leading to the development of premalignant lesions and subsequent tumors. Surgery, radiation, and chemotherapy are conventional therapies used against oral cancer, though they have numerous side effects. Cisplatin, a genotoxic agent, is one of the most potent chemotherapy drugs, and has been widely used alone or in combination with other antineoplastic drugs or radiation therapy to treat various cancer types. However, this drug causes adverse effects that limit its therapeutic efficiency. To overcome such limitations of this drug and to find the new route of drug delivery systems based on microemulsions and nanoparticles have been explored toward modulating the enhanced permeability and retention effect and promoting cisplatin delivery to tumors. Cancer chemoprevention, which represents one promising approach, is defined as the prevention, inhibition or reversal of carcinogenesis by intervention with chemically derived or naturally occurring dietary substances. The purpose of this study to prepare the buccal patches to treat oral cancer which should effective against the oral cancer and can use easily to the patient who should faced this problem. A buccal patches has been prepare and the chemical components are (carbopol 934, polyethylene glycol, glycerin, methyl paraben, propyl paraben, HPMC, Cisplatin, etc) were analyzed by high performance liquid chromatography in further study.